RECOMMENDATIONS OF THE DEVELOPMENT OF INTERPROFESSIONAL EDUCATION IN A FACULTY OF MEDICINE - Hikmah Muktamiroh; Agneta Irmarahayu; Yuni Setyaningsih (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: In the Competence Standards of Indonesian Doctor (SKDI) which will ratify, interprofessional communicationand collaboration are competencies that Indonesian doctors mustown. Therefore, the implementation of interprofessional education (IPE) is a must for medical education institutions. Medical Faculty of the Universitas Pembangunan Nasional Veteran Jakarta (FK UPNVJ) has not specifically built the IPE module but has introduced aspects for interprofessional collaboration in the curriculum. Evaluation of the perceptions and readiness of students about IPE learning in students of academic year 2, 3 and 4 using the Indonesian version of The Interdisciplinary Education Perception Scale (IEPS) and Readiness for Interprofessional Learning Scale (RIPLS) showed that there were no differences in IEPS scores on student years 2nd and 3rd but decreased in 4th year students and the best RIPLS scores in the 3rd year and decreased in the 4th year. Against these results, intervention recommendations are needed to obtain results following the demands and expectations.Objectives: This study aims to obtain recommendations made based on disscussion and analysis of teaching staff of the FK UPNVJ about the results of evaluating perceptions and readiness of the FK UPNVJ at the academic stage.Methods: The research was a phenomenological qualitative research. Data collection through the opened-ended on Focus Group Discussion and in-depth interviews with teaching staff of the FK UPNVJ.Results: The teaching staff stated the importance of implementing interprofessional education by forming a curriculum. The curriculum must be more focused on interprofessional communication and collaboration since the academic stage. This implementation can be done well if get full support from the dean and the rector. The teacher staff, dean and rector’s commitment to the implementation of interprofessional education is the demand as well as the hope for the implementation of interprofessional educationConclusion: The obligation to implement interprofessional education is not natural, but it is not impossible. Several things can be done so that doctors graduating from FK UPNVJ can own communication and interprofessional collaboration competencies.